Development of Mathematics Student Worksheets Based on Mathematical Understanding with a Worked Example Approach - Lubis, Rahma Aulia; Wahyuni, Sri (Lembaga Riset Mutiara Akbar, 2022)
This development research was conducted to produce a product, determine the validity, and student responses to the teaching materials of the student worksheets that have been produced. This study developed a Mathematics Student Worksheet based on mathematical understanding abilities with a worked example approach on the material of a two-variable linear equation system that could be an alternative to minimize students' cognitive load and provide understanding to students. The subjects of this study were students of class VIII-2 SMP Swasta PAB 3 Saentis which consisted of 10 students, where the researchers chose respondents based on a small scale. The methodology used is research and development which was developed using the ADDIE development model consisting of five steps, namely: (1) analysis, (2) design, (3) development, (4) implementation (implementation), and (5) evaluation. However, in this study, it was carried out until the development stage. The results of this study showed that the mathematical student worksheets based on mathematical understanding abilities with the worked example approach on the material of a two-variable linear equation system according to media expert validation were in the percentage of 80% with good validation categories. , or suitable for use without revision and material expert validation is in the percentage of 87% with a good validation category, or suitable for use without revision. As for the RPP, according to the validation of media experts and material experts, the percentage is 82.22% with a good category, or suitable for use without revision. And according to student responses, the percentage is 86% with very good criteria, it can be used in the learning process. So that with these data, this study can fulfill the assumption that students' worksheets based on mathematical understanding abilities with a worked example approach on the material of a two-variable linear equation system are feasible and effective in terms of cognitive content and student understanding in the learning process